2017
DOI: 10.1016/j.ccell.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GPC2 as an Oncoprotein and Candidate Immunotherapeutic Target in High-Risk Neuroblastoma

Abstract: Summary We developed an RNA sequencing-based pipeline to discover differentially expressed cell surface molecules in neuroblastoma that meet criteria for optimal immunotherapeutic target safety and efficacy. Here we show that GPC2 is a strong candidate immunotherapeutic target in this childhood cancer. We demonstrate high GPC2 expression in neuroblastoma due to MYCN transcriptional activation and/or somatic gain of the GPC2 locus. We confirm GPC2 to be highly expressed on most neuroblastomas, but not detectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
220
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 170 publications
(236 citation statements)
references
References 41 publications
6
220
0
Order By: Relevance
“…Chromatin immunoprecipitation was performed on adherent cells as described in Bosse et al, 2017(Bosse et al 2017). Of note, a different MYCN antibody was used than listed in Bosse et al, 2017 (Santa Cruz B8.4B, sc-53993).…”
Section: Mycn Chip-seq: Kelly and Ngp Cell Linesmentioning
confidence: 99%
“…Chromatin immunoprecipitation was performed on adherent cells as described in Bosse et al, 2017(Bosse et al 2017). Of note, a different MYCN antibody was used than listed in Bosse et al, 2017 (Santa Cruz B8.4B, sc-53993).…”
Section: Mycn Chip-seq: Kelly and Ngp Cell Linesmentioning
confidence: 99%
“…Moreover, analysis of ChIP-Seq data found that MYCN binds to the promoter of PBK in neuroblastoma cell lines, and is accompanied by the active enhancer histone mark, H3K27Ac ( Fig. 6H) (20), suggesting direct transcriptional upregulation of PBK by MYCN.…”
Section: Two Neuroblastoma Oncogenes Lin28b and Mycn Regulate The Ementioning
confidence: 94%
“…(13) PBK promoter luciferase assays were carried out as previously described, with PBK promoter luciferase values normalized to CellTiter-Glo luminescence assay values. (20)…”
Section: 'Utr and Promoter Luciferase Reporter Assaysmentioning
confidence: 99%
See 2 more Smart Citations